Ice and snow thickness measurements from the ArcWatch-2 Expedition - Jonathan Kolar; Niklas Neckel; Janna Elisabeth Rückert; Linnea Bühler; Jonathan Bahlmann; Nils Risse; Stefan Hendricks; Mara Neudert (PANGAEA, 2025)
Here we present data from sled based multi-frequency electro magnetic induction measurements (GEM-2, Geophex Ltd.) for all ice stations visited during the ArcWatch-2 (PS144) Polarstern Expedition to the central Arctic Ocean. Between 2024-08-16 and 2024-09-26 Polarstern was moored to 10 larger ice floes on which the GEM-2 surveys were conducted. Prior to each survey the device was calibrated using a standardized procedure (e.g. Itken et al., 2023). The GEM-2 measures the distance from the snow surface to the ice–ocean interface resulting in a total ice+snow thickness estimate. We therefore included additional snow thickness measurements from a Magnaprobe device carried out along the same transects as the GEM-2 measurements. Both datasets were drift corrected and referenced to local GNSS stations employed at each ice station (Neckel et al., 2025).